An Experimental Evaluation of AGA Algorithm for RSS Positioning in GSM Networks - Brida, P.; Machaj, J.; Benikovsky, J.; Duha, J. (Elektronika ir Elektrotechnika, 2010)
The quality of location based services depends on the positioning accuracy of mobile station estimation. Generally, there are several methods suitable for cellular networks. The more accurate methods are way more expensive to implement. On the contrary, there are methods with lower accuracy and much lower costs as well. Received Signal Strength method belongs to the second case. The purpose of this paper is to experimentally evaluate adaptive geometric algorithm implemented into RSS method. The algorithm is an improved version of basic geometric algorithm and it is compared to it as well as to standard Least Squares method. The properties of the proposed algorithm are evaluated in two different environments: urban and rural. The environments have absolutely different signal propagation conditions and the algorithm performance was validated in the representative samples of environment.